A clinicoepidemological study of Lichen planus pigmentosus and its association with metabolic syndrome and cutaneous manifestations in Indian population - Rozy Badyal; Ramesh Kumar Kushwaha; Arti Singh Rajput; Suresh Kumar Jain; Asha Nyati; Devendra Yadav (Wolters Kluwer Medknow Publications, 2020)
Background: Lichen planus pigmentosus (LPP) is considered an infrequent variant of Lichen planus (LP) clinically characterized by insidious onset of discrete, ill-defined, and dark brown or slate gray macules, primarily appearing over sun-exposed areas and flexures. Materials and method: This was a cross-sectional study conducted over a period of 1 year from July 2017 to July 2018 among the patients attending the OPD of the Department of Dermatology, Government Medical College, Kota, India. This study evaluated the LPP and its association with metabolic syndrome and cutaneous manifestations. Serum high-density lipoprotein (HDL)-cholesterol (HDL-C) and triglycerides (TG) were measured with enzymatic procedures. Plasma glucose was measured using hexokinase method. Results: There were 16 (32.0%) males and 34 (68.0%) females affected with LPP. Majority of the patients were in the age group of 40 to 49 years [15 (30.0%)] and above 50 years [16 (32.0%)]. Diabetes mellitus type 2 was reported among 17 (34.0%), hypertension among five (10.0%), and obesity among five (10.0%) patients. Increased low-density lipoprotein (LDL) and very LDL was found among 15 (30.0%) patients and decreased HDL was found among 19 (38.0%) patients. Conclusion: A 34.0% prevalence of metabolic syndrome was found in patients with LP. Central obesity, increased fasting blood sugar (FBS), and low HDL-C were the metabolic syndrome parameters found to be more common in patients with LP in our study.